2000
DOI: 10.1093/heapol/15.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Cost recovery in Mauritania: initial lessons

Abstract: Cost recovery was introduced in Mauritania in 1993. Analysis of the Mauritanian experience provides a number of key points to the discussion surrounding the contribution of user fees to health care systems. Initial results appear to be largely positive regarding the improvement of the quality of health care and the overall level of utilization of basic health establishments. They suggest that users are globally willing to pay when the quality of health care improves, and that, contrary to a frequently voiced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 15 publications
0
19
1
1
Order By: Relevance
“…In order to detect the existence, the nature and the intensity of any impoverishment effect on patients' preferences with respect to improving the quality of delivered care, a binary variable indicating the phase of the study, i.e., early-or late-uprising, was also introduced into the model. 3 This was followed by an assessment of all possible interactions between, on the one hand, the study phase, and on the other hand, respondents' demographic and socioeconomic characteristics and the level of quality improvements. The interaction terms allow us to understand the factors whose effects on WTP varied following impoverishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to detect the existence, the nature and the intensity of any impoverishment effect on patients' preferences with respect to improving the quality of delivered care, a binary variable indicating the phase of the study, i.e., early-or late-uprising, was also introduced into the model. 3 This was followed by an assessment of all possible interactions between, on the one hand, the study phase, and on the other hand, respondents' demographic and socioeconomic characteristics and the level of quality improvements. The interaction terms allow us to understand the factors whose effects on WTP varied following impoverishment.…”
Section: Discussionmentioning
confidence: 99%
“…Many governments responded by implementing stabilization and structural adjustment programs [3], proposed and subsequently demanded by international organizations, e.g., the World Bank [4] and the International Monetary Fund [5]. Hence, these states were obliged to restrict their social expenditures including health care budgets [6], with the risk of compromising the provision of good quality care.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of DRF scheme has led to a situation whereby the healthcare workers are carrying out work far in excess of their original schedule of work for which they have little or no training on, especially management of drug revolving funds which involves a lot of basic accounting skill and record keepings. It has been shown that cost recovery accompanied by a fair supply of essential drugs (as in DRF scheme) and by a better motivated staff improved the efficiency of the health system in Mauritania [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus a study led in Bamako (Mali) has shown that, short of making visible and immediate improvements of the quality of health care provided by health care services, the introduction of user fees would inevitably lead to a reduction of the demand for health care (Mariko, 2003). On the other hand, an increase in attendance, thanks to the financial incentives distributed to the staff which led to improved services, was elsewhere observed (Litvack and Bodart, 1993;Audibert and Mathonnat, 2000;Chawla and Ellis, 2000;Kipp et al, 2001). In Mauritania, the introduction of financial contribution, by permitting a strong availability of generic essential drugs and re-motivation of the staff, had contributed to improving the quality of health care and the level of use of health care facilities during several years (Audibert and Mathonnat, 2000).…”
Section: Effectiveness and Effects Of Pricing Policymentioning
confidence: 78%
“…This orientation, called 'Bamako Initiative' (BI), was supposed to be articulated, inter alia, around the setting up of a coherent price policy between the different levels of the health pyramid, decentralization of empowerment down to the most appropriate level to reach policy targets, minimization of costs through generic essential drugs policies (EGD) and communal participation. The fixing of a price scale for health care should contribute to improved availability of drugs and quality health care because of the injection of additional financial resources into health care facilities (Audibert and Mathonnat, 2000). If user fees for health care was subject to a lot of controversy mainly because of equity concerns 1 (Diop et al, 1995;Creese, 1997;Gilson, 1997;Chawla and Ellis, 2000;Nyonator and Kutzin, 2003), the debate focused little on the method of assessing the prices of care in order to improve the functioning of health facilities by increasing resources without increasing inequity.…”
Section: Introductionmentioning
confidence: 99%